Flow Simulation Study For Rotating Cage Equipment - Mohamed Razak, Mohd Hairie Azam (2018)
Corrosion is an unavoidable event that occur specifically in pipelines. There are multi-faceted factors contributing to corrosion in pipelines. Several techniques can be used to simulate the pipeline flow. One of the methods is Rotating Cage (RC), which can be used to simulate pipeline flow by rotating a sample cage in a beaker filled with test solution as described in ASTM G184. Computational fluid dynamics (CFD) software: ANSYS Fluent has been used to study the hydrodynamics of the existing and improved version of rotating cage. The project aims to analyse and compare different designs of rotating cage in terms of velocity, flow profile, and wall shear stress distribution using computational fluid dynamics (CFD) technique. For the existing design, the simulated velocity agreed well with the theoretical velocity but showed discrepancies in terms of wall shear stress up to 80 percent as the velocity increased. The discrepancies arose because of several factors which were the equation to calculate theoretical value did not provide good approximation, and the design itself affected the wall shear stress distribution. A new design has been proposed to mitigate this problem by increasing the number of installed coupons and reducing the gap between them. There was no significance improvement compared to the previous design but it showed slightly high wall shear on the coupon. The equation model for shear stress has been revised to fit the result from the simulations with R-squared value 0.94.